2013
DOI: 10.1097/shk.0b013e318289376b
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Pathologies of the Myocardium in Septic Shock

Abstract: Myocardial depression in septic shock is well known, but its pathophysiological genesis is incompletely understood. To assess the incidence and extent of stress-induced histologic myocardial alterations in septic shock, a prospective, observational, combined clinical and postmortem study was conducted, and 20 patients dying from septic shock were included. Exclusion criteria were younger than 18 years, pregnancy, open heart surgery or cardiopulmonary resuscitation, acute neurologic diseases, pheochromocytoma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 22 publications
1
46
1
4
Order By: Relevance
“…It is most likely that the increase in intrathoracic pressure causing significantly increased PAP, MAP, PA, and regional blood flows, minute ventilation, and higher oxygen delivery, as well, may have contributed to less epinephrine administration in the SI group. Further, Schmittinger et al 39 recently demonstrated histological features of stress-induced cardiotoxicity correlated with doses of epinephrine administration, thus cautioning about the potential adverse effects with the use of epinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…It is most likely that the increase in intrathoracic pressure causing significantly increased PAP, MAP, PA, and regional blood flows, minute ventilation, and higher oxygen delivery, as well, may have contributed to less epinephrine administration in the SI group. Further, Schmittinger et al 39 recently demonstrated histological features of stress-induced cardiotoxicity correlated with doses of epinephrine administration, thus cautioning about the potential adverse effects with the use of epinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms that account for cholestasis induced by liver ischemia are not well understood. [38,39] Iwashyna and colleagues reported that cholestasis was induced by acute liver ischemia. [40] Fouassier and colleagues examined the expression of hepatobiliary transporter genes, such as the Na + -transporting polypeptide (NTCP, also called Slc10a1), the bile salt export pump (BSEP), and the multidrug resistance-associated protein MRP2 (also called ABCC2), which are important for bile formation in the liver of rats 24 h after arterial deprivation.…”
Section: Regulation Of Hepatic Drug Metabolism By Liver I/rmentioning
confidence: 99%
“…Inne obserwowane zmiany to m.in. martwica, krwawienie i włóknienie śródmiąższowe, myocarditis (wg niektórych autorów do 1/3 przypadków) czy też infekcyjne zapalenie wsierdzia [13,19]. Do badania histopatologicznego zaleca się pobranie pełnej grubości wycinków w postaci poprzecznych do przebiegu włókien mięś-niowych plastrów, minimum 5 wycinków -2 z prawej komory i 3 z różnych części lewej komory [20].…”
Section: Histopathological Examinationunclassified
“…The histopathological examination of the heart reveals interstitial infiltrations of mononucleated cells, which -in the majority of cases -are not related to myocarditis but to the process of generalized vascular endothelial dysregulation. Other observed lesions include necrosis, interstitial haemorrhaging and fibrosis, myocarditis (according to some authors, in up to a third of all cases) or infectious endocarditis [13,19]. The recommended procedure for performing a histopathological examination is to collect full-thickness specimens in the form of slices transverse to the arrangement of muscle fibres, a total of five specimens: two from the right ventricle and three from various parts of the left ventricle [20].…”
Section: Histopathological Examinationmentioning
confidence: 99%